The stratigraphic and paleoenvironmental significance of the regressive Monte Observación Member, Early Miocene of the Austral Basin, Patagonia (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The stratigraphy of the Oligocene-Miocene southern Patagonia marine deposits has been extensively discussed. However, the Monte Observación Member (MOM) was vaguely defined and many aspects related to its boundaries, distribution, lithology and paleoenvironments of deposition remain uncertain. In this paper we present results obtained from the field survey of several early Miocene outcrops exposed along the Atlantic coast of southern Santa Cruz Province (Austral-Magallanes Basin). They correspond to the transitional interval between the marine shelf Monte León Formation and the terrestrial Santa Cruz Formation. Sedimentological analysis allowed to define six Facies Associations (FAs) for the studied beds: FA-1 corresponds to inner shelf to lower shoreface deposits; FA-2 corresponds to prodelta to distal delta-front deposits; FA-3 corresponds to proximal delta-front deposits; FA-4 corresponds to terminal distributary channels and meandering channels in the delta plain; FA-5 corresponds to inter-distributary bays and tidal flats; and finally FA-6 corresponds to the upper delta plain deposits. In turn, analysis of fossil concentrations allowed defining three main genetic types: biogenic, sedimentologic, and mixed biogenic-sedimentologic concentrations. Biogenic concentrations are represented by beds and lenses of the marginal marine oyster Crassostrea orbignyi (Ihering), which is a significant fossil invertebrate typical of the transitional deposits and is the last invertebrate showing marine influence in all the studied sections and beyond. Sedimentologic and mixed biogenic-sedimentologic concentrations exhibit different attributes and evidence the action of different processes. They include from mostly monospecific within-habitat reworked concentrations, with little post-morten disturbance to polyspecific concentrations bearing the imprint of various taphonomic processes. The distribution of FAs suggest a regressive system that prograded over shelf deposits in the form of deltaic depositional systems with tidal influence. This analysis allowed to define better the MOM, which shows: 1) null to very low bioturbation degrees; 2) a reduced autochthonous invertebrate faunal content; 3) a well-stratified pattern given by the alternating lithologies, and 4) abundant decimetric intercalations of gray to greenish sandstone beds. The fast accumulation of the MOM, which would be part of the regressive phase of the Monte León Formation, could be the consequence of a peak of siliciclastic and volcaniclastic input into the Austral Basin, produced as a result of rapid exhumation of the Southern Patagonian Andes during the early Miocene.